Urinary capillariosis in a free-ranging Marsican brown bear (Ursus arctos marsicanus) - Mariacher, Alessia; Eleni, Claudia; Fico, Rosario; Perrucci, Stefania (International Journal for Parasitology: Parasites and Wildlife, 2018)
Extraintestinal nematodes have been seldom investigated in the brown bear (Ursus arctos). In this study, a case of urinary capillariosis and bladder associated lesions is reported in a deceased free-ranging Marsican brown bear (Ursus arctos marsicanus) from Central Italy. Gross lesions in the urinary bladder consisted of scattered foci of mucosal hyperemia, while at histological examination mild cystitis was observed. At microscopic examination of urine and bladder lavage fluid, capillariid adult female nematodes and eggs were found, suspected of belonging to the genus Pearsonema based on their location in the urinary bladder. This is the first report of Pearsonema infection and associated bladder lesions in a brown bear.